Barriers and Facilitators to Implementing Functional Family Therapy in a Community Setting: Client and Practitioner Perspectives. (9th March 2017) - McPherson, Kerri E.; Kerr, Susan; Casey, Beth; Marshall, John
Abstract : While Functional Family Therapy (FFT) is known to be effective in addressing adolescent behavioral problems, there has been little exploration of issues relevant to its transport from the tightly controlled setting of clinical trials into routine service delivery. This study sought the views of key stakeholders, clients, and practitioners, on barriers and facilitators to the successful implementation of FFT. Undertaken in a community setting in Scotland, interviews were carried out with 12 adolescents, 14 parents/caregivers, and 6 practitioners. Results focus on: Referral process and pre‐intervention contact; Engagement of families; Structure and delivery; Organizational factors. Although barriers to engagement were identified, FFT was viewed as an acceptable, appropriate and feasible intervention with the potential to improve adolescent wellbeing in 'real‐world' settings.